2017
DOI: 10.1038/s41598-017-11343-5
|View full text |Cite
|
Sign up to set email alerts
|

Leaf thermotolerance in tropical trees from a seasonally dry climate varies along the slow-fast resource acquisition spectrum

Abstract: Knowledge of the upper limits of temperature tolerance is essential to understand how tropical trees will respond to global warming. We quantified leaf thermotolerance in 41 tree species growing in a seasonally dry tropical region of the Indian subcontinent to examine: (1) differences between evergreen and deciduous species; (2) relationships with leaf mass per area (LMA) and leaf size; and, (3) seasonal variation in thermotolerance. Thermotolerance ranged from 45.5 °C to 50.5 °C among species, was higher for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
89
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 54 publications
9
89
4
1
Order By: Relevance
“…More recently, O'Sullivan et al () reported seasonal variations in T crit at two sites (temperate woodland and a tropical rainforest) in Australia (three species at each site) consistent with thermal acclimation patterns, with the seasonal adjustments being similar to the biome‐to‐biome patterns of T crit values measured in summer at each site. Similar results were recently reported by Sastry and Barua () assessing seasonal variations in P HT at a dry tropical forest in India. By contrast, seasonal measurements of T crit in leaves of a subalpine evergreen tree in Australia revealed that heat tolerance was higher in trees experiencing ice‐encasement in winter than warmer conditions in summer (O'Sullivan et al, ).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…More recently, O'Sullivan et al () reported seasonal variations in T crit at two sites (temperate woodland and a tropical rainforest) in Australia (three species at each site) consistent with thermal acclimation patterns, with the seasonal adjustments being similar to the biome‐to‐biome patterns of T crit values measured in summer at each site. Similar results were recently reported by Sastry and Barua () assessing seasonal variations in P HT at a dry tropical forest in India. By contrast, seasonal measurements of T crit in leaves of a subalpine evergreen tree in Australia revealed that heat tolerance was higher in trees experiencing ice‐encasement in winter than warmer conditions in summer (O'Sullivan et al, ).…”
Section: Introductionsupporting
confidence: 91%
“…A further issue is how acclimation might affect the thermal safety margin of T crit —calculated as the difference between P HT and maximum habitat temperatures (O'Sullivan et al, ; Sastry & Barua, ). Based on both field and glasshouse study, we found the acclimation pattern to rising growth temperatures results in increases in P HT that are below unity (~0.3 °C per °C), rising air temperatures (e.g., due to global warming) are likely to reduce the thermal safety margin, with the impact of this reduction on leaf function being greatest in summer than winter as leaves experience temperatures that approach the maximal values of P HT .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, growth temperature can influence leaf thickness, and thinner leaves are often more susceptible to high temperature damage, especially when light is high and wind speed is low (Curtis, Leigh, & Rayburg, ; Leigh et al, ; Sastry & Barua, ). Yet, leaves collected for our respiration measurements provided no evidence that warm‐ and cool‐grown leaves differed in LMA.…”
Section: Discussionmentioning
confidence: 99%
“…Even when high temperatures reduce A , some tree species maintain high g s (and transpiration) which helps cool leaves (Drake et al, ; Urban, Ingwers, McGuire, & Teskey, ). There is also evidence that trees can tolerate temperatures much higher than they typically experience (O'Sullivan et al, ) and may acclimate to high temperatures by increasing the thermal limits of leaf function (e.g., photosynthesis, respiration; Drake et al, ; Sastry & Barua, ; Zhu et al, ). Isoprene and HSPs may facilitate acclimation to high temperatures; yet, associations between I s , HSP production, and changes in the thermal limits of leaf function in response to heatwave conditions have not been tested.…”
Section: Introductionmentioning
confidence: 99%
“…35 °C thylakoid membranes have been observed to structurally change (Gounaris, Brain, Quinn, & Willams, , ), and above 40 °C photosystem II (PSII) may become deactivated and the electron transport rate reduced (Allakhverdiev et al, ). Chlorophyll fluorescence parameters to assess heat tolerance of PSII show critical temperature thresholds in the region of 45–60 °C, with significant variation between species (O'Sullivan et al, ; Sastry & Barua, ). Irreversible thermal damage to photosynthetic machinery has been observed to occur at 52 °C in a tropical species (Krause et al, ).…”
Section: Introductionmentioning
confidence: 99%